Peningkatan Kapasitas Mama-Mama Melalui Pembuatan Nugget Ikan Di Kampung Matara Merauke Papua Selatan - Situmorang, Prima Lestari; Puspa, Leonora; Hanip, Rival; Nainggolan, herrio tekdi; Sijabat, Survey; Elya Puspita, Laurensia; Thalib, Najdah (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
Matara Village, located in Merauke Regency, South Papua Province, is a coastal community with abundant marine resources, particularly fish as a primary commodity. However, limited processing capacity results in fish being sold whole at low prices or even unsold leading to economic losses and declining household incomes. The inability to process fish into nutritious, high-value products remains a key challenge. To address this issue, a team of lecturers from Musamus University conducted a community empowerment program focusing on training local women ("mama-mama") to produce fish nuggets. The program included field observations, counseling sessions, technical demonstrations, direct mentoring, and a satisfaction survey. As a result, nutritious and marketable fish nugget samples were successfully produced. This initiative aims to foster entrepreneurship and improve local economic resilience. The community responded positively and expressed strong interest in sustained support from relevant institutions for ongoing development.